A Dynamic Calibration Method for Injection‐Dependent Charge Carrier Lifetime Measurements. Issue 9 (24th July 2021) - Zhu, Yan; Trupke, Thorsten; Hameiri, Ziv
Abstract: Charge carrier lifetime is an important parameter for semiconductor materials. This study proposes a dynamic calibration method for injection‐dependent carrier lifetime measurements. This method is based on the comparison between lifetime measurements under quasi‐steady‐state and non‐quasi‐steady‐state conditions. The proposed method is first demonstrated by numerical simulation. Experimental data are subsequently used to compare the proposed method with conventional calibration methods, demonstrating good agreement between the methods. Furthermore, the calibration method is found to be much less sensitive to measurement noise. When applied to photoluminescence‐based carrier lifetime measurements, the proposed method also provides the net bulk doping concentration. Abstract : Measuring the injection‐dependent charge carrier lifetime is an essential characterization technique for semiconductor materials. This paper proposes a dynamic lifetime calibration method. The proposed method is much less sensitive to measurement noise compared to conventional methods. Bulk doping information is also not required and can even be extracted if the proposed method is used for photoluminescence‐based measurements.